Predictors of adolescent well-being around the globe: are students from Confucian East Asia different? - Rudolf, Robert (Frontiers in Psychology, 2024)
Purpose: Using rich data from nearly 400,000 15-year-olds across 70 middle-and high-income countries and economies participating in PISA 2018, this study investigates (1) global predictors of adolescent subjective well-being (SWB), and (2) differences in adolescent life satisfaction, its predictors and endowments with predictors across world regions and cultures. A particular focus lies on comparing Confucian East Asia (CEA) with other world regions.Methods: Data were analyzed using multiple linear regressions and Blinder-Oaxaca decomposition. As measures of adolescent well-being, this study employs life satisfaction, affective well-being, and meaning in life.Results: Globally, adolescent well-being outcomes are found to be most strongly linked to gender, personality, relative SES, relationship quality, peer SWB, autonomy and the learning environment, as well as local cultural factors. Estimations by world region reveal several culture-specific explanations for interregional well-being gaps. In particular, notoriously low levels of life satisfaction among students from CEA countries are found to be associated with low self-efficacy, low peer well-being, as well as with high emotional interdependence compared to other world regions. Emotional interdependence is more strongly experienced among CEA adolescents compared to adolescents from any other world region. Moreover, it is found to be more strongly associated with life satisfaction in the CEA region than in any other region. In line with the former, CEA students show stronger links between other relational factors (parents' emotional support; sense of belonging at school) and life satisfaction compared to most other regions.Implications: This study suggests that among the environmental factors that shape the experience of adolescent lives, relationship and cultural factors play key roles and are closely intertwined.Parents, educators and policymakers around the world should focus on creating a positive school environment that promotes well-being, student self-efficacy, a sense of belonging, and a safe space in which failure is accepted as part of the learning process. This is particularly needed in Confucian East Asian countries.